Perfecting Imperfect Competition - Goetz Seißer (Kiel Institute for the World Economy (IfW), 2008)
This paper addresses the reduction of market failure under imperfect competition. It proposes a taxscheme that provides firms with an incentive to forgo their market power: Firms optimize after-tax profits. Now simply consider a firms gross profit margin the unique tax-rate it is charged on absolute profits. In theory the firms tax-rate would be the mark-up over marginal costs, the firms Lerner index. As a result every firm determines its own tax-rate by setting its price and incurring costs. This creates a new trade off for firms between a low tax-burden and the exercising of market power. Welfare for society increases since firms with market power choose a lower price and produce a quantity closer or equal to social optimum; at the original monopolistic price-level they can increase their profits by lowering their tax-burden. Essentially the tax-condition does not seem to distort profit incentives or markets; under perfect competition the tax-rate would be zero. Thus, it is clear that the tax only takes effect when markets work inefficiently and its countervailing nature subsequently helps to remedy inefficiencies of imperfectly competitive markets.
Keywords: H21; D40; D21; P11; H26; H25; D00; 330; Imperfect competition; market power; tax-condition; monopoly; welfare; efficiency; Steuerpolitik; Unvollkommener Wettbewerb; Optimale Besteuerung; Marktmacht; Wohlfahrtseffekt; Theorie